2008
DOI: 10.4161/cc.7.5.5488
|View full text |Cite
|
Sign up to set email alerts
|

The electrostatic surface of MDM2 modulates the specificity of its interaction with phosphorylated and unphosphorylated p53 peptides

Abstract: Lane (2008) The electrostatic surface of MDM2 modulates the specificity of its interaction with phosphorylated and unphosphorylated p53 peptides, Cell Cycle, 7:5, 608-610, DOI: 10.4161/cc.7.5.5488To link to this article: https://doi.org/10.4161/cc.7.5.5488 Florescence anisotropy measurements using FAM-labelled p53 peptides showed that the binding of the peptides to MDM2 was dependant upon the phosphorylation of p53 at Thr18 and that this binding was modulated by the electrostatic properties of MDM2. In agreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 8 publications
2
25
0
Order By: Relevance
“…Phosphorylation of Thr18 significantly reduces the affinity of TAD for MDM2 because of electrostatic repulsion between the phosphate group and a negatively charged patch on the MDM2 surface (Sakaguchi et al 2000;Schon et al 2002;Brown et al 2008). In contrast, phosphorylation at Thr18 and other sites within TAD can significantly enhance the affinity of TAD for p300 and its various subdomains (Ferreon et al 2009;Jenkins et al 2009;Lee et al 2009;Teufel et al 2009).…”
Section: Signaling Diversity Through Intrinsic Disordermentioning
confidence: 99%
“…Phosphorylation of Thr18 significantly reduces the affinity of TAD for MDM2 because of electrostatic repulsion between the phosphate group and a negatively charged patch on the MDM2 surface (Sakaguchi et al 2000;Schon et al 2002;Brown et al 2008). In contrast, phosphorylation at Thr18 and other sites within TAD can significantly enhance the affinity of TAD for p300 and its various subdomains (Ferreon et al 2009;Jenkins et al 2009;Lee et al 2009;Teufel et al 2009).…”
Section: Signaling Diversity Through Intrinsic Disordermentioning
confidence: 99%
“…The suggestion that phosphorylation of these sites destabilizes p53-MDM2 interaction is supported by alanine mutagenesis experiments 23 and computer simulations. 18,24,39,40 The physical rationale for the destabilization of binding is usually ascribed to thermodynamic effects 18 however, kinetic effects have not been studied in either experimental or simulation studies. In this study, we turn our attention to at least one model that describes the kinetic aspects: the structure and dynamics of the p53-MDM2 'encounter complex' before and after p53 phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…23 Computational models, partly validated by experiments, suggested that the effect of phosphorylation was attributed to enhancing elecrostatic repulsion in the region where Thr18 docks by placing the negatively charged phosphorylated Thr18 near anionic regions of the MDM2 surface. 18,24 Phosphorylation of Ser20, however, was found to be sufficient to disrupt the p53-MDM2 interaction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations